2019
DOI: 10.1016/j.jprot.2019.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of saliva from dogs with and without obesity-related metabolic dysfuntion

Abstract: Dogs develop only some of the components of the human metabolic syndrome (MetS). Thus, in order to study possible MetS-related alterations in dogs, human MetS criteria were adapted to define canine MetS or so-called obesity-related metabolic dysfunction (ORMD). The main objective of this study was to identify changes in the salivary proteome of obese dogs with ORMD in comparison with obese dogs without ORMD which may constitute potential salivary biomarkers for assessing ORMD. In a first phase, 12 adult obese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Excess canine adiposity leads to a shorter life span [7][8][9] and is linked to a number of different comorbidities, such as respiratory dysfunction [10][11][12], orthopaedic disease [8,13] and metabolic dysfunction [14][15][16]. In addition, breed-specific health problems can be exacerbated when dogs are overweight or obese.…”
Section: Introductionmentioning
confidence: 99%
“…Excess canine adiposity leads to a shorter life span [7][8][9] and is linked to a number of different comorbidities, such as respiratory dysfunction [10][11][12], orthopaedic disease [8,13] and metabolic dysfunction [14][15][16]. In addition, breed-specific health problems can be exacerbated when dogs are overweight or obese.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies on patients with leishmaniosis and babesiosis found a significant downregulation of Apolipoprotein A, which may reduce the individual's capacity to respond to oxidative damage. Beyond the field of infectious diseases, proteomic analysis has provided new insights in veterinary nephrology, revealing that an increase in proteins like retinol-binding protein predicts kidney damage before azotemia develops (Nabity et al, 2011;Chacar et al, 2017;Ferlizza et al, 2020), and in veterinary endocrinology, uncovering the role of Apolipoprotein I in canine obesity (Tvarijonaviciute et al, 2012;Lucena et al, 2019). According to the literature, the most commonly analyzed samples in veterinary medicine are serum and saliva (González-Arostegui et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…In humans, insulin resistance is considered the primary cause of metabolic syndrome, which in turn is correlated with abdominal obesity (TVARIJONAVICIUTE et al, 2019). Insulin resistance is characterized by decreased ability to metabolize blood glucose (LUCENA et al, 2019). Rahmouni et al (2005) also state that insulin resistance has been shown to be a key factor for the development of the components of the syndrome.…”
Section: Original Articlementioning
confidence: 99%
“…In any case, obesity is considered the main triggering factor of this dysfunction (TVARIJONAVICIUTE et al, 2016;PIANTEDOSI et al, 2020). Currently, four parameters that occur in dogs are considered: systemic arterial hypertension, hyperlipidemia, insulin resistance and obesity (LUCENA et al, 2019).…”
Section: Introductionmentioning
confidence: 99%